Efektivitas Terapi Antituberkulosis Empirik pada Pasien dengan Penyakit HIV Stadium Lanjut: Sebuah Laporan Kasus Berbasis Bukti - Chandra, Natasha; Elita, Dina; Yunihastuti, Evy (UI Scholars Hub, 2024)
Patients with advanced human immunodeficiency virus (HIV) disease have a high risk of mortality, with tuberculosis (TB) being one of the leading causes. Empiric antituberculosis therapy could be considered as a strategy to reduced mortality although there is no strong evidence. This study aims to review the efficacy of empiric antituberculosis therapy in patient with advanced HIV disease compared to isoniazid prophylaxis therapy and assessed with mortality as outcome. A 46- year old male patient with advanced HIV disease on antiretroviral therapy (ARV) and liver cirrhosis was admitted to hospital due to difficulties in sleeping and walking. During hospitalization he had seizure followed by decreased consciousness hence TB meningitis was suspected. Latest laboratory results showed CD4 count of 132 cells/mm3 and negative TB examinations. He was given empiric antituberculosis therapy but later died during hospitalization. A systematic literature searching was conducted in PubMed, ScienceDirect, Scopus, Cochrane, and EMBASE using keywords according to clinical question resulting in 69 studies. Study selection was conducted according to eligibility criteria and two studies with open-label randomized trial design were selected. Eligible studies were critically appraised using the Oxford Center for Evidence-Based Medicine Critical Appraisal Worksheet. Both studies had good validity. In patients with advanced HIV disease, mortality at week 24 was 5.2% (95%CI 3.5-7.8%) in empiric antituberculosis therapy group and 5.2% (95%CI 3.4-7.8%) in isoniazid prophylaxis therapy group, with an absolute risk difference of -0.06% (95%CI −3.05-2.94%; p=0.97). Meanwhile, mortality at week 96 was 10.1% (95%CI: 7.5- 13.6%) in empiric antituberculosis therapy group and 10.5% (95%CI 7.9-13.9%) in isoniazid prophylaxis therapy group, with absolute risk difference of 0.4% (95%CI −3.8-4.6%; p=0.86). Based on critical appraisal on both studies, it can be concluded that empiric antituberculosis therapy is not effective in significantly reducing mortality compared to isoniazid prophylaxis therapy in patients with advanced HIV disease.